New Insights Into Culturable and Unculturable Bacteria Across the Life History of Medicinal Maggots Lucilia sericata (Meigen) (Diptera: Calliphoridae) - Maleki-Ravasan, Naseh; Ahmadi, Nahid; Soroushzadeh, Zahra; Raz, Abbas Ali; Zakeri, Sedigheh; Dinparast Djadid, Navid (Frontiers in Microbiology, 2020)
Due to the nutritional ecology of dung- and carrion-feeding, bacteria are the integral part of Lucilia sericata life cycle. Nevertheless, the disinfected larvae of the blowfly are applied to treat human chronic wounds in a bio-surgery named maggot debridement therapy (MDT). To realize the effects of location/diet on the gut bacteria, to infer the role of bacteria in the blowfly ecology plus in the MDT process, and to disclose bacteria circulating horizontally in and vertically between generations, bacterial communities associated with L. sericata specimens from various sources were investigated using culture-based and culture-independent methods. Totally, 265 bacteria, including 20 families, 28 genera, and 40 species, were identified in many sources of the L. sericata. Culture-dependent method identified a number of 144 bacterial isolates, including 21 species, in flies reared in an insectary; specimens were collected from the field, and third-instar larvae retrieved from chronic wounds of patients. Metagenetic approach exposed the occurrences of 121 operational taxonomic units comprising of 32 bacterial species from immature and adult stages of L. sericata. The Gammaproteobacteria was distinguished as the dominant class of bacteria by both methods. Bacteria came into the life cycle of L. sericata over the foods and transovarially infected eggs. Enterococcus faecalis, Myroides phaeus, Proteus spp., Providencia vermicola, and Serratia marcescens were exchanged among individuals via the transstadial transmission. Factors, including diets, feeding status, identification tool, gut compartment, and life stage, governed the bacteria species. Herein, we re-emphasized that L. sericata is thoroughly connected to the bacteria both in numerous gut compartments and in different life stages. Among all, transstadially transmitted bacteria are underlined, indicating the lack of antagonistic effect of the larval excretions/secretions on these resident bacteria. While the culture-dependent method generated useful data on the viable aerobic gut bacteria, metagenomic method enabled us to identify bacteria directly from the tissues without any need for cultivation and to facilitate the identification of anaerobic and unculturable bacteria. These findings are planned to pave the way for further research to determine the role of each bacterial species/strain in the insect ecology as well as in antimicrobial, antibiofilm, anti-inflammatory, and wound healing activities.